Navigating the rivers of sustainability in the Amazon: the dilemma of accounting for carbon credits - Santana, Aleff dos Santos; Círico, Juh; Miranda, Claudio de Souza; Souza, Alessandra de Fátima Souza de; Silva Belo, Rayane de Lima (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2025)
Purpose: The education case in this paper aims to encourage discussions about accounting for carbon credits by presenting a fictional story about a female accountant who is head of an ecologically sustainable family business called Econorte. Lecturers and students from accounting courses will be able to discuss the bookkeeping issues for sustainable companies that use carbon credits. Methodology: This educational case uses a mixed methodology, starting with a reflection on the importance of studies on accounting for carbon credits, which include classification, bookkeeping, and explanations/justifications for these records. Results: The data presented in this educational case serves as a basis to reflect on, classify, record and justify the importance of accounting for carbon credits. Study Contributions: This paper is an instrument that can be applied to undergraduate business courses, mainly the Accounting Sciences such as Environmental Accounting, Environmental Management, Socio-environmental Responsibility and Sustainable Development.